Using Rap Music to Better Understand African American Experiences. Issue 4 (1st October 2020) - Brooks, Michael; Wolfgang, Jeff; Adams, Justin; Armstrong, Noreal; Cassidy, Rochelle
ABSTRACT: This content analysis was conducted to identify and explore messages in rap music surrounding police brutality. Analysis from the 10 selected songs revealed the potential for these messages to improve the cultural competency of counselors, the ability of counselors to better understand future Black clients, and the benefits of featuring rap music and hip hop culture in future counseling research. Three major themes were identified based on the lyrical content analysis; feelings of validation, rightful retaliation, and wrongful manipulation. According to the results, the counseling profession can stand to revisit its cultural assessment and sensitivity if they wish to be more aware of the needs of Black clients.